Analysis of genetic diversity among pomegranates cultivated in Diyala, Iraq using RAPD-PCR method - Zainab M. Hamid; Silva A. Y. Zokian (World Journal of Experimental Biosciences, 2015)
This study attempts to identify genetic diversity among four genotypes of pomegranates cultivated in Diyala city, Iraq and find the genetic polymorphism among them by using DNA markers generated by polymerase chain reaction (PCR). Total genomic DNA of genotypes studied was extracted from dry young leaves by using cetyltrimethyl ammonium bromide (CTAB) procedure. Molecular analysis was performed by using twelve random markers in random amplified polymorphic DNA (RAPD-PCR) technique. The analyses based on five primers OPH – 08, OPH – 13, OPH – 18, RI – 3 and RI – 16, which used in amplification and polymorphism for the four cultivated genotypes studied. The genetic polymorphisms value of each primer was determined and ranged between 31 to 100%; primers OPBA–3 and OPBB–4 produced the highest percent of genetic polymorphism compared with primer OPH–13. The genetic diversity and the isolation of the four cultivated genotypes of pomegranates were confirmed obviously by RAPD-PCR technique.
Keywords: Genotypes, Pomegranates, RAPD-PCR technique.